Analysis of 500 kV OHTL polluted insulator string behavior during lightning strokes. (February 2018) - Said, A.
Highlights: The relation between 500 kV insulator string leakage current and flashover was analyzed. All case studies were done under normal condition and different lightning strokes. The harmonic spectrum and of clean and polluted 500-kV string insulators leakage current were detected. The relation between back flashover and insulator surface condition were discussed. Polluted insulator thermal losses magnitudes were 97.2% higher than in clean insulator. Low lightning strokes peak leaded to serious insulator flashover in case of polluted. Abstract: The lightning strokes can be very harmfull to the high voltage transmission lines especially in case polluted insulator string. In this paper, the lightning overvoltage in the El-Kuorimate - Cairo 500-kV transmission line single circuit is discussed. The leakage current and its harmonic spectrum on clean and polluted 500-kV string insulators are determined under normal condition and lightning strokes. Furthermore, the relation between back flashover and insulator surface condition are discussed under different magnitude of lightning strokes. The results show that the leakage current, thermal losses magnitudes in case polluted insulator are higher than in case clean insulator by about 97.2%. For polluted insulator, less lightning strokes peak will increase leakage current to above 60 mA, and lead to serious insulator flashover faster than clean insulator. This study based on an equivalent electrical model by using Alternative Transients Program (ATP-EMTP) software.